Adipose‐derived regenerative cells and lipotransfer in alleviating breast cancer‐related lymphedema: An open‐label phase I trial with 4 years of follow‐up. (17th February 2021) - Jørgensen, Mads Gustaf; Toyserkani, Navid Mohamadpour; Jensen, Charlotte Harken; Andersen, Ditte Caroline; Sheikh, Søren Paludan; Sørensen, Jens Ahm
Abstract: Patients with breast cancer‐related lymphedema (BCRL) have reduced quality of life and arm function. Current treatments are palliative, and treatments improving lymphedema are lacking. Preclinical studies have suggested that adipose‐derived regenerative cells (ADRCs) can alleviate lymphedema. We, therefore, aimed to assess whether ADRCs can alleviate lymphedema in clinical reality with long‐term follow‐up. We treated 10 patients with BCRL using ADRCs and a scar‐releasing lipotransfer to the axillary region, and all patients were followed 1, 3, 6, 12, and 48 months after treatment. The primary endpoint was change in arm volume. Secondary endpoints were safety, change in lymphedema symptoms, quality of life, lymphedema‐associated cellulitis, and conservative treatment use. There was no significant decrease in BCRL volume after treatment. However, self‐reported upper extremity disability and arm heaviness and tension improved. Six patients reduced their use of conservative BCRL treatment. Five patients felt that their BCRL had improved substantially, and four of these would redo the treatment. We did not observe any cases of locoregional breast cancer recurrence. In this phase I study with 4 years of follow‐up, axillary delivered ADRCs and lipotransfer were safe and feasible and improved BCRL symptoms and upper extremity function. Randomized controlled trials are needed to confirm the results of this study. Abstract : This graphical abstract shows the improvements in patients self‐reported lymphedema symptoms and arm function. P = P value